Legionella spp. All Ears? The Broad Occurrence of Quorum Sensing Elements outside Legionella pneumophila. (18th February 2021) - Herran, Benjamin; Grève, Pierre; Berjeaud, Jean-Marc; Bertaux, Joanne; Crépin, Alexandre
Abstract: Legionella spp. are ubiquitous bacteria principally found in water networks and ∼20 species are implicated in Legionnaire's disease. Among them, Legionella pneumophila is an intracellular pathogen of environmental protozoa, responsible for ∼90% of cases in the world. Legionella pneumophila regulates in part its virulence by a quorum sensing system named "Legionella quorum sensing, " composed of a signal synthase LqsA, two histidine kinase membrane receptors LqsS and LqsT and a cytoplasmic receptor LqsR. To date, this communication system was only found in L. pneumophila . Here, we investigated 58 Legionella genomes to determine the presence of a lqs cluster or homologous receptors using TBlastN. This analysis revealed three categories of species: 19 harbored a complete lqs cluster, 20 did not possess lqsA but maintained the receptor lqsR and/or lqsS, and 19 did not have any of the lqs genes. No correlation was observed between pathogenicity and the presence of a quorum sensing system. We determined by RT-qPCR that the lqsA gene was expressed at least in four strains among different species available in our laboratory. Furthermore, we showed that the lqs genomic region was conserved even in species possessing only the receptors of the quorum sensing system, indicating an ancestral acquisition and various loss dynamics during evolution. This system could therefore function in interspecific communication as well.